High-brightness anti-skid ceramic tile and process thereof

By using two-layer glaze structure, polishing and waxing treatment on the tiles, nanoparticle etching liquid to form etching pits of microstructures and filling them with anti-slip wax, the problem of low anti-slip performance of existing high-gloss tiles is solved, and the coexistence of high-gloss, anti-slip and delicate texture is achieved, and the overall performance and service life of the tiles are improved.

CN119775054AActive Publication Date: 2025-04-08GUANGDONG HAOSHENG CERAMICS CO LTD

Patent Information

Application Number
CN202411995354.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

When pursuing anti-slip performance, existing high-gloss tiles often damage the integrity of their surface, resulting in low anti-slip performance, and it is difficult to achieve the coexistence of high-gloss, anti-slip and delicate texture at the same time.

Method used

A two-layer glaze structure is adopted, and the bottom glaze contains dry particles to improve the brightness effect. The fine pores are filled by polishing and waxing treatment, and the etching pits of microstructure are combined with nanoparticle etching liquid to form an etching pit to enhance the roughness, and the etching pits are filled with anti-slip wax to form a thick anti-slip wax layer.

Benefits of technology

It realizes the coexistence of high-gloss, ultra-slip and delicate texture, improves the anti-slip, anti-fouling and transparent effect of ceramic tiles, and extends the service life of ceramic tiles.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

According to the highlight anti-skid ceramic tile and the process thereof, the highlight anti-skid ceramic tile has the advantage of highlight, also has a super anti-skid effect and a fine texture, and coexistence of multiple characteristics is achieved. Comprising the following preparation steps: (1) taking a molded green brick, applying ground glaze and cover glaze, and firing to obtain a standard ceramic tile, the thickness of the cover glaze being 8-12mm; (2) the ceramic tile is polished, the polishing thickness is 1 / 9-1 / 7 of the thickness of the cover glaze, and the ceramic tile is obtained; (3) waxing the surface of the ceramic tile; (4) coating an etching solution containing particles, wherein the etching time is 5-15 seconds; (5) drying and cleaning the surfaces of the ceramic tiles; and (6) applying anti-skid wax, drying and curing to prepare the high-brightness anti-skid ceramic tile.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic tiles, and in particular to a high-gloss anti-skid ceramic tile and a process thereof. Background Art

[0002] Ceramic tiles have a long history in my country. The essence of ceramic tiles is to imitate natural marble, imitating the texture of marble, and have properties that are superior to natural marble. As people's quality of life improves, the quality and characteristics of ceramic tiles are more valued.

[0003] Among conventional ceramic tiles, wear resistance, glossiness, and anti-slip are all common characteristics of ceramic tiles, but these characteristics restrict each other and are often difficult to coexist. High gloss is a characteristic of modern ceramic tiles, which has a high requirement for glossiness. High gloss ceramic tiles are highly ornamental and widely sold. For example, they are used in the decoration of large shopping malls, the walls of buildings, and home decoration.

[0004] Since it is high gloss, it means that the surface flatness of the tile is particularly high, which will lead to low anti-slip performance. Therefore, the industry will also adjust its anti-slip coefficient in various ways, such as using mixed acidic liquid as an anti-slip agent, using acidic substances to corrode the ground, but this will more or less damage the integrity of the brick body, and long-term use can easily cause various problems.

[0005] Therefore, technicians in this field are also studying how to break through existing technologies and produce tiles with multiple characteristics. Summary of the invention

[0006] The invention discloses a high-brightness anti-skid tile and a process thereof, which has both excellent brightness advantages and super anti-skid effect and more delicate texture, thereby achieving the coexistence of multiple characteristics.

[0007] A production process of a high-gloss anti-slip tile of the present invention comprises the following preparation steps:

[0008] (1) taking a formed brick, applying a base glaze, applying a surface glaze, and firing to obtain a quasi-ceramic tile, wherein the thickness of the surface glaze is 8-12 mm;

[0009] (2) polishing the aligned ceramic tile to a thickness of 1 / 9 to 1 / 7 of the glaze thickness to obtain the ceramic tile;

[0010] (3) Waxing the surface of the tiles;

[0011] (4) applying an etching solution containing particles, and the etching time is 5-15 seconds;

[0012] (5) Dry and clean the surface of the tiles;

[0013] (6) Apply anti-slip wax, dry and solidify to make high-gloss anti-slip tiles.

[0014] Preferably, an inkjet-printed pattern is included between the bottom glaze and the top glaze.

[0015] Preferably, the glaze comprises a bottom glaze and an upper glaze;

[0016] The bottom glaze comprises 20-35 parts of dry particles, 5-20 parts of glaze slurry, and 30 parts of printing ink in parts by weight;

[0017] The upper layer glaze comprises 10-30 parts of glaze slurry and 100 parts of printing ink in parts by weight;

[0018] The thickness of the bottom layer glaze and the upper layer glaze are substantially the same.

[0019] Preferably, the particle size of the dry particles passes through a 100-250 mesh sieve.

[0020] Preferably, the particles described in step (4) are nanoparticles with a diameter of 50-200 nm.

[0021] Preferably, the weight ratio of nanoparticles: etching solution = 1:8-20.

[0022] Preferably, the coating in step (4) is performed at a speed of 10-30 m / s for 2-5 seconds, and then the etching solution is retained for 3-10 seconds.

[0023] Preferably, the waxing thickness in step (3) is 0.3-1.5 mm higher than the surface glaze layer.

[0024] Preferably, the anti-slip wax is in a wax water state.

[0025] The present invention also provides a high-brightness anti-slip tile, which is prepared by the production process of the high-brightness anti-slip tile described above.

[0026] The high-gloss anti-skid ceramic tile and its process disclosed by the present invention adopts a two-layer structure of the surface glaze of the brick body, the bottom surface glaze ensures the high-gloss effect, the brick body is polished to make the upper surface glaze reveal a large number of fine pores, and then waxing is performed to fill the wax into the fine pores, thereby solving the problem of fine pores absorbing dirt on the surface glaze layer of the brick body, and then the etching liquid and nanoparticles are used to form microscopic etching pits on the surface of the ceramic tile to enhance the roughness, thereby improving the anti-skid performance of the ceramic tile and stabilizing the subsequent anti-skid wax, and then after cleaning, water-like anti-skid wax is injected to fully fill the etching pits, and a thick anti-skid wax layer is formed on the surface of the brick body after drying and solidification. Combined with the structure of the entire ceramic tile, the ceramic tile has excellent anti-skid effect, excellent anti-fouling effect, and also has an anti-transmission effect. DETAILED DESCRIPTION

[0027] The invention discloses a high-brightness anti-skid tile and a process thereof, which has the advantages of high brightness, super anti-skid effect and delicate texture.

[0028] The present invention provides a production process for high-gloss anti-slip tiles, comprising the following preparation steps:

[0029] (1) taking a formed brick, applying a base glaze, applying a surface glaze, and firing to obtain a quasi-ceramic tile, wherein the thickness of the surface glaze is 8-12 mm;

[0030] (2) polishing the aligned ceramic tile to a thickness of 1 / 9 to 1 / 7 of the thickness of the glaze layer to obtain the ceramic tile;

[0031] (3) Waxing the surface of the tiles;

[0032] (4) applying an etching solution containing particles, and the etching time is 5-15 seconds;

[0033] (5) Dry and clean the surface of the tiles;

[0034] (6) Apply anti-slip wax and dry the anti-slip wax layer to make high-gloss anti-slip tiles.

[0035] Preferably, an inkjet-printed pattern is included between the bottom glaze and the top glaze.

[0036] Preferably, the glaze comprises a bottom glaze and an upper glaze;

[0037] The bottom glaze comprises 20-35 parts of dry particles, 5-20 parts of glaze slurry, and 30 parts of printing ink in parts by weight;

[0038] The upper layer glaze comprises 10-30 parts of glaze slurry and 100 parts of printing ink in parts by weight;

[0039] The thickness of the bottom layer glaze and the upper layer glaze are substantially the same.

[0040] Preferably, the particle size of the dry particles passes through a 100-250 mesh sieve.

[0041] Preferably, the particles described in step (4) are nanoparticles with a diameter of 50-200 nm.

[0042] Preferably, the weight ratio of nanoparticles: etching solution = 1:8-20.

[0043] Preferably, the coating in step (4) is performed at a speed of 10-30 m / s for 2-5 seconds, and then the etching solution is retained for 3-10 seconds.

[0044] Preferably, an alkaline etching solution is used.

[0045] Preferably, the waxing thickness in step (3) is 0.3-1.5 mm higher than the surface glaze layer.

[0046] Preferably, the anti-slip wax is in a wax water state.

[0047] The present invention also provides a high-brightness anti-slip tile, which is prepared by the production process of the high-brightness anti-slip tile described above.

[0048] The dry granules may include the following components by weight: SiO 2 35-45 parts, Al 2 O 3 22-26 copies, K 2 O is 1.5-2 parts, Na 2 O is 0.4-1.0 parts, CaO is 13-17 parts, MgO is 1.35-1.5 parts, and ZnO is 4.5-7 parts.

[0049] The glaze slurry includes the following components calculated by weight: 28-43 parts of potassium feldspar, 2-8 parts of wollastonite, 4-11 parts of barium carbonate, 2-8 parts of zinc oxide, 5-12 parts of kaolin, and 18-26 parts of quartz; and also includes components of a thickener and a degumming agent.

[0050] It should be noted that it is difficult for existing tiles to have high hardness, high brightness and high anti-slip effects at the same time. Therefore, the present invention takes a different approach and adopts a method different from the prior art to achieve the coexistence of different effects.

[0051] The ceramic tile of the present application is firstly produced according to the conventional brick blank, base glaze and inkjet printing pattern mode. The top glaze adopts two layers of glaze. The bottom layer adopts dry particles as the highlight basis. The polishing is mainly performed on the upper layer of glaze. Since there are no dry particles in the upper layer of glaze, the integrity of the dry particles can be guaranteed. The pores exposed by polishing can also be guaranteed to be uniform. The polishing depth is 1 / 9 to 1 / 7 of the thickness of the top glaze, so that it can effectively expose more uniform pores of the brick body, and then it can be guaranteed that the surface material of the top glaze layer is the same and the ability to withstand external force is the same.

[0052] Next, apply wax to the surface of the glaze layer of the brick body and allow it to penetrate into the pores. A wax is preferred, but homopolymer wax can also be used. This solves the problem of dirt hiding in the pores on the surface of the brick body, achieves the initial anti-fouling performance of the entire tile, and at the same time maintains a relatively thin thickness so that the etching liquid in the subsequent process can form a good coating structure.

[0053] Next, an etching solution mixed with nanoparticles is coated on the surface of the brick, the diameter of the nanoparticles is 50-200nm, preferably 50-100nm, the weight ratio of nanoparticles: etching solution is 1:10-20, and first impact at a rate of 10-30 m / s for 2-5 seconds, that is, spray for 2-5 seconds, spraying refers to the comprehensive spraying of the entire brick surface, and then the etching solution is retained on the surface of the brick for 3-10 seconds, so that a large number of microscopic etching pits appear on the surface of the brick, thereby enhancing the roughness of the brick surface and the anti-slip performance. At the same time, it also provides a guarantee for the subsequent anti-slip wax processing, which is beneficial to the stability of the anti-slip wax, thereby improving the overall durability of the tile.

[0054] Then, preferably, a rubber scraper is used to remove the liquid on the surface of the brick body, and then a grinding head is used to almost completely clean the etching liquid and particles to prepare for the next process.

[0055] Finally, use water-based anti-skid wax to drip onto the surface of the brick, use a grinding head to evenly spread the wax water and allow it to penetrate and fully fill the etched pits. It is best to repeat the operation multiple times, and finally dry and solidify it to form an anti-skid wax layer to achieve an anti-skid effect, and can also play an anti-fouling and anti-transparency role.

[0056] The ceramic tile of the present invention has fine pores on the ceramic tile body coated with wax after the polishing process, so that there are fewer places for dirt to hide between the fine pores and the wax. However, due to the different materials, finer water vapor can still penetrate. When there are fine pores in the ceramic tile and water vapor is hidden, it acts like the adsorption of a small suction cup, achieving the first layer of anti-slip effect.

[0057] When the etching liquid is applied to the brick by spraying and impacting, the nanoparticles hit the surface of the brick due to the impact effect, forming uniform pits. In addition, the etching liquid "corrodes" the surface of the brick, forming countless nano-sized pores. After cleaning, apply water-based anti-slip wax. After the anti-slip wax is fully filled into the pits and the surface of the brick, it is dried and solidified, that is, it is dried and solidified to form an anti-slip wax layer, achieving a second layer of anti-slip effect.

[0058] Moreover, this anti-slip wax layer is like growing little feet, and the part that "sinks" into the holes is firmly fixed on the brick body like little feet, and is very stable; further, even if the anti-slip wax layer is worn out under long-term and strong friction, the product structure formed by the glaze layer of the brick body and the etched pits on the microstructure is difficult to wear out, so it has a longer lifespan than conventional anti-slip tiles.

[0059] Because the brick body, that is, the quasi-ceramic tile itself has the effects of brick blank, base glaze, inkjet and surface glaze, the surface glaze adopts two layers, and the bottom layer contains dry particles. The dry particles have higher reflection and refraction effects, so that when the light hits the tile, the reflectivity is strong, thus the brightness is high.

[0060] Therefore, the ceramic tile made by the present invention has both bright and anti-slip effects, and also maintains good anti-fouling performance and high transparency, thus solving the common problems of brightness and anti-slip, and is also a technological breakthrough.

[0061] It effectively solves the problem of uneven pores left over from the production of ordinary tiles, and solves the problem of easy accumulation of dirt and discoloration after long-term use.

[0062] Example 1

[0063] A production process of high-gloss anti-slip tiles, comprising the following preparation steps:

[0064] (1-1) taking a formed brick, applying a base glaze, inkjet printing a pattern, applying a surface glaze, and firing to obtain a quasi-ceramic tile, wherein the thickness of the surface glaze is 8-12 mm;

[0065] The glaze includes a bottom glaze and an upper glaze;

[0066] The bottom glaze comprises, by weight, 20-35 parts of 100-250 mesh dry particles, 5-20 parts of glaze slurry, and 30 parts of printing ink;

[0067] The upper layer glaze comprises 10-30 parts of glaze slurry and 100 parts of printing ink in parts by weight;

[0068] The thickness of the bottom glaze and the upper glaze are substantially the same;

[0069] (1-2) polishing the aligned ceramic tile, with the polishing thickness being 1 / 9 to 1 / 7 of the glaze thickness, to obtain the ceramic tile;

[0070] (1-3) Waxing the surface of the tiles;

[0071] The thickness of waxing is 0.3-1.5mm above the surface glaze layer;

[0072] (1-4) applying an etching solution containing nanoparticles with a diameter of 50-200 nm, impacting at a speed of 10-30 m / s for 2-5 seconds, then retaining the etching solution for 3-10 seconds, and maintaining the etching time for 5-15 seconds;

[0073] The weight ratio of nanoparticles: etching solution = 1:8-20;

[0074] (1-5) Dry and clean the tile surface;

[0075] (1-6) Apply anti-slip wax, dry and solidify to make high-gloss anti-slip tiles;

[0076] The anti-slip wax is in the form of wax water.

[0077] Example 2

[0078] A production process of high-gloss anti-slip tiles, comprising the following preparation steps:

[0079] (2-1) taking a formed brick, applying a base glaze, inkjet printing a pattern, applying a surface glaze, and firing to obtain a standard tile, wherein the surface glaze has a thickness of 10 mm;

[0080] The glaze includes a bottom glaze and an upper glaze;

[0081] The bottom glaze comprises 28 parts of 150 mesh dry particles, 15 parts of glaze slurry, and 30 parts of printing ink in parts by weight;

[0082] The upper layer glaze comprises 25 parts of glaze slurry and 100 parts of printing ink in parts by weight;

[0083] The thickness of the bottom glaze and the upper glaze are substantially the same;

[0084] (2-2) polishing the aligned ceramic tile, with the polishing thickness being 1 / 8 of the glaze thickness, to obtain the ceramic tile;

[0085] (2-3) Waxing the surface of the tiles;

[0086] The thickness of waxing is 0.5mm above the surface glaze layer;

[0087] (2-4) applying an etching solution containing nanoparticles with a diameter of 150 nm, impacting at a rate of 25 m / s for 4 seconds, then retaining the etching solution for 10 seconds, and the etching time is maintained for 14 seconds;

[0088] The weight ratio of nanoparticles: etching solution = 1:16;

[0089] (2-5) Dry and clean the tile surface;

[0090] (2-6) Apply anti-slip wax, dry and solidify to make high-gloss anti-slip tiles;

[0091] The anti-slip wax is in the form of wax water.

[0092] Example 3

[0093] A production process of high-gloss anti-slip tiles, comprising the following preparation steps:

[0094] (3-1) taking a formed brick, applying a base glaze, inkjet printing a pattern, applying a surface glaze, and firing to obtain a quasi-ceramic tile, wherein the thickness of the surface glaze is 8-12 mm;

[0095] The glaze includes a bottom glaze and an upper glaze;

[0096] The bottom glaze comprises 33 parts of 100 mesh dry particles, 18 parts of glaze slurry, and 30 parts of printing ink in parts by weight;

[0097] The upper layer glaze comprises 28 parts of glaze slurry and 100 parts of printing ink in parts by weight;

[0098] The thickness of the bottom glaze and the upper glaze are substantially the same;

[0099] (3-2) polishing the aligned ceramic tile, the polishing thickness is 1 / 9 of the glaze thickness, and obtaining the ceramic tile;

[0100] (3-3) Waxing the surface of the tiles;

[0101] The thickness of waxing is 1mm above the surface glaze layer;

[0102] (3-4) applying an etching solution containing nanoparticles with a diameter of 100 nm, impacting at a rate of 15 m / s for 4 seconds, then retaining the etching solution for 10 seconds, and the etching time is maintained for 14 seconds;

[0103] The weight ratio of nanoparticles: etching solution = 1:15;

[0104] (3-5) Dry and clean the tile surface;

[0105] (3-6) Apply anti-slip wax, dry and solidify to make high-gloss anti-slip tiles;

[0106] The anti-slip wax is in the form of wax water.

[0107] The above is a detailed introduction to a high-gloss anti-slip tile and its process provided by the present invention. For a person skilled in the art, according to the idea of ​​the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A production process for high-gloss anti-slip tiles, characterized in that: The method comprises the following preparation steps: (1) taking a formed brick, applying a base glaze, applying a surface glaze, and firing to obtain a quasi-ceramic tile, wherein the thickness of the surface glaze is 8-12 mm; (2) polishing the aligned ceramic tile to a thickness of 1 / 9 to 1 / 7 of the glaze thickness to obtain the ceramic tile; (3) Waxing the surface of the tiles; (4) applying an etching solution containing particles, and the etching time is 5-15 seconds; (5) Dry and clean the surface of the tiles; (6) Apply anti-slip wax, dry and solidify to make high-gloss anti-slip tiles.

2. The production process of high-gloss anti-slip tiles according to claim 1 is characterized in that: An inkjet printing pattern is also included between the bottom glaze and the top glaze.

3. The production process of high-gloss anti-slip tiles according to claim 1 is characterized in that: The glaze includes a bottom glaze and an upper glaze; The bottom glaze comprises 20-35 parts of dry particles, 5-20 parts of glaze slurry, and 30 parts of printing ink in parts by weight; The upper layer glaze comprises 10-30 parts of glaze slurry and 100 parts of printing ink in parts by weight; The thickness of the bottom layer glaze and the upper layer glaze are substantially the same.

4. The production process of high-gloss anti-slip tiles according to claim 3 is characterized in that: The particle size of the dry particles is sieved through a 100-250 mesh sieve.

5. The production process of high-gloss anti-slip tiles according to claim 1 is characterized in that: The particles described in step (4) are nanoparticles with a diameter of 50-200 nm.

6. The production process of high-gloss anti-slip tiles according to claim 5 is characterized in that: The weight ratio of nanoparticles: etching solution = 1:8-20.

7. The production process of high-gloss anti-slip tiles according to any one of claims 1 to 6, characterized in that: The coating in step (4) is performed at a rate of 10-30 m / s for 2-5 seconds, and then the etching solution is retained for 3-10 seconds.

8. The production process of high-gloss anti-slip tiles according to claim 1, characterized in that: The waxing thickness in step (3) is 0.3-1.5 mm higher than the surface glaze layer.

9. The production process of high-gloss anti-slip tiles according to claim 1, characterized in that: The anti-slip wax is in a wax water state.

10. A high-gloss anti-slip tile, characterized in that: The high-gloss anti-slip ceramic tile is prepared by the production process of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Material surface sand surface matte processing method and device

    CN108724014A

  • Preparation method of soft-light anti-skid ceramic tile

    CN115403409A

  • Preparation method of high-brightness non-slip brick

    CN115872619A

  • Antiskid ceramic tile and preparation method thereof

    CN117486634A

  • Ceramic tile and methods for its manufacture

    DE102010013524A1

Cited By

  • Antiskid antifouling bright ceramic tile and preparation method thereof

    CN121698678A